Cerebral near-infrared spectroscopy guided neonatal intensive care management for the preterm infant - Pellicer, Adelina; Boode, Willem de; Dempsey, Eugene; Greisen, Gorm; Mintzer, Jonathan; Naulaers, Gunnar; Pichler, Gerhard; Roehr, Charles Christoph; Roll, Claudia; Schwarz, Christoph; Costa, Cristine Sortica da; Kooi, Elisabeth (Pediatric research, 2024)
Infants requiring admission to the neonatal intensive care unit (NICU) are particularly vulnerable to developing brain injury. The severity of the underlying clinical conditions and the complexity of care call for continuous, cot-side, non-invasive monitoring tools. Near-infrared spectroscopy (NIRS) measures the regional tissue oxygen saturation of hemoglobin (rStO2) and provides continuous information on the net-result of several factors. Cerebral rStO2 correlates with echocardiography-derived measures of blood flow. Cerebral fractional tissue oxygen extraction provides information on the balance between oxygen supply and demand and can be continuously derived from the combined use of cerebral rStO2 and arterial oxygen saturation. Information on cerebral blood flow autoregulatory capacity can be obtained from combining cerebral rStO2 and invasive blood pressure monitoring by appropriate software. Cerebral rStO2 provides real-time, end-organ information on perfusion-oxygenation, and when interpreted in the clinical context based on pathophysiological principles may be used as a help to guide interventions in the NICU. In this review we will discuss how to optimize NIRS monitoring for application in the NICU, with a particular focus on the preterm infant.
Online veröffentlicht: 7. November 2024
Gesehen am 20.08.2025